PENGARUH BIAYA LINGKUNGAN DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN DENGAN KINERJA LINGKUNGAN SEBAGAI PEMEDIASI ( Studi Empiris Pada Perusahaan Terdaftar di BEI yang Mengikuti PROPER Tahun 2016-2018) - Meri, Handayani; Ria, Sari Nelly; Eka, Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this research is to analyse the effect of environmental cost and corporate social responsibility (CSR) disclosure on financial performance with environmental performance as a mediated (empirical study on companies listed on Indonesia Stock Exchange which following PROPER year 2016-2018)". This research is a quantitative study using secondary data observed from the company's annual report. The population in this study is the companies listed on the Indonesia Stock Exchange which following PROPER year 2016-2018. The sample in this study were 52 companies with a total sampel is 156 data. The sampling technique used was purposive sampling technique. The analytical method used is multiple linear regression and sobel test. The results of this research indicate that environmental cost and environmental performance have an effect on financial performance because the value of thitung>ttabel with a significance value of <0.05, while the disclosure of corporate social responsibility (CSR) has no effect on financial performance but has an effect on environmental performance. Environmental cost have no effect on environmental performance, while disclosure of corporate social responsibility (CSR) effect on environmental performance. Environmental performance is able to mediate between disclosure of corporate social responsibility (CSR) on financial performance but unable to mediate environmental cost on financial performance.Keywords: Environmental Costs, Disclosure Of Corporate Social Responsibility (CSR), Environmental Performance (PROPER) and Financial Performance (ROE).